Blood atherogenic potential as a predictor of arterial hypertension among children living in ecologically unsafe territories of the Moldova Republic - L. V. Vasilos; M. G. Arame; A. N. Kozhokaru; A. I. Khorodishtyanu-Banukh; O. N. Kyrtsya (Российский кардиологический журнал, 2013)
According to WHO, arterial hypertension (AH) determines the structure of morbidity, mortality, and disability of adult populations. However, the origins of AH stem from the childhood, as the development period of regulatory mechanisms and structural disorders. Aim. To assess the blood atherogenic potential among children living in ecologically unsafe regions and to investigate the role of metabolic disorders in the AH development. Material and methods. In total, health status was assessed in 1500 children from ecologically unsafe regions of theMoldovaRepublic. All Moldovan regions were divided into 3 categories: moderate xenobiotic pollution; heavy xenobiotic pollution; and a control zone. Morbidity assessment was based on standard methods and unified diagnostic criteria. In addition, physical development, blood pressure, autonomic haemostasis, metabolic status, and atherogenic index were assessed. Results. AH was diagnosed in 3,1% of the examined children, and its prevalence was higher in more polluted regions. Among children and adolescents from ecologically unsafe regions, a relatively high prevalence of metabolic syndrome, reduced antioxidant protection, and pronounced hypothalamic dysfunction suggested an important role of xenobiotics in the AH development during childhood. Metabolic syndrome was characterised by a significant increase in the levels of lipids and low-density lipoproteins, as well as by elevated levels of total cholesterol and triglycerides. Atherogenic index was doubled in children from ecologically unsafe regions, compared to their peers from the control group. In all children with AH, dyslipidemia was observed. Compared to healthy children, atherogenic index was 2,4 and 1,7 times higher in hypertensive children with overweight or normal body weight, respectively. Conclusion. Assessment of blood atherogenic potential in children from ecologically unsafe regions could be used for the prediction of AH development and progression.